Sociodemographic characteristics of adolescents living with alcoholic families in the city of João Pessoa, Paraíba - Pereira, Vagna Cristina Leite da Silva; Costa, Lorena de Farias Pimentel; Alves, Estela Rodrigues Paiva; Cordeiro, Camila Abrantes; Braga, Luanna Silva; Filha, Maria de Oliveira Ferreira (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2015)
The aim of this study is to estimate the amount of teens that inhabit homes with alcoholic families in a representative sample of adolescents in the city of João Pessoa, Paraíba; then characterize the demographic profiles of these adolescents and their alcoholic families. This is a cross-sectional population-based study, conducted with 715 teenagers between the ages of 14 to 19 years old. A sociodemographic questionnaire and CAGE-family instrument were used. For data analysis, descriptive statistics were used. According tothe results, most of the teenagers were girls, age 17 years old, and within the alcoholic family, the father was most referenced. It is necessary to implement preventive measures for the health of teens with alcoholic family members, taking into account the risk for the development of biopsychosocial problems.